2015
DOI: 10.1002/pssa.201532071
|View full text |Cite
|
Sign up to set email alerts
|

Screen printing insulator coatings for electrofluidic display devices

Abstract: The screen printing of amorphous fluoropolymer films as insulators for electrofluidic display device use is demonstrated. Screen printing enables the hydrophobic dielectric to be directly patterned at device level with the required film thickness as well as excellent material utilisation. The films give very good electrical performance, with high uniformity and dielectric strength, and the resulting devices exhibit comparable electro‐optic behaviour to those fabricated with spin‐coated films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The uniformity of the dielectric layer can be further improved by optimizing the mesh design parameters, the coating fluid properties, and the printing process. As observed previously [ 19 ], the main parameters that affect the thickness of the film are the free mesh volume and the polymer concentration in the coating solution, rather than the printing pressure and speed. We found that in terms of the “pin-hole free” property of the coating, the FP coating processed by screen printing was even better than that prepared by the traditional spin-coating method.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…The uniformity of the dielectric layer can be further improved by optimizing the mesh design parameters, the coating fluid properties, and the printing process. As observed previously [ 19 ], the main parameters that affect the thickness of the film are the free mesh volume and the polymer concentration in the coating solution, rather than the printing pressure and speed. We found that in terms of the “pin-hole free” property of the coating, the FP coating processed by screen printing was even better than that prepared by the traditional spin-coating method.…”
Section: Resultsmentioning
confidence: 70%
“…Some key issues that are important for the commercialization of electrofluidic arrays are simplifying the fabrication process, improving material utilization, and increasing the homogeneity of the coatings over large areas. In our previous work [ 19 , 20 ], we reported the possibility of using screen printing to simultaneously coat and pattern fluoropolymer (FP) films as insulators for EFD devices on 6 inch square substrates. This reduced the coating time from ~4 min/plate to less than 1 min/plate while increasing the material utilization from 22% to >52%.…”
Section: Introductionmentioning
confidence: 99%
“… Schematic plot of electrowetting display. (Images are reproduced from reference [ 6 ] with the permission of Wiley-VCH Verlag). …”
Section: Figurementioning
confidence: 99%
“…The current preparation of dielectric layers is a lengthy and error-prone process which includes sample cleaning, film coating, surface treatment and photolithographic patterning [ 5 ]. Chen et al [ 6 ] reported the advantages of screen printing techniques for preparing uniform and compact dielectric materials as compared with the conventional spin coating process. Guo et al [ 7 ] selectively injected a fluoropolymer to form hydrophobic patterns based on a combined approach of inkjet printing and phase change filling.…”
Section: Introductionmentioning
confidence: 99%
“…71 Recently, many researchers have demonstrated fabrication of transistors through screen printing at different scales. 72 Among the non-contact approaches, screen printing, in which screen mask is used to print materials onto large-area substrates with high throughput, is considered as one of the scalable 3D printing techniques and has been the most widely used technology in various domains such as flexible sensors, actuators, electrofluidic devices, 73 batteries, 74 and supercapacitors. 75 Chang et al demonstrated the fabrication of large area flexible pressure sensors by utilizing screen printing technique.…”
Section: Additive Manufacturing Fabrication Technologiesmentioning
confidence: 99%